2007
DOI: 10.1061/(asce)0733-9453(2007)133:4(159)
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Low-Cost GPS Receiver Accuracy and Precision in Forest Environments

Abstract: Selecting the appropriate receiver is an issue when a major portion of global positioning system ͑GPS͒ data collection is below forest canopies. This study compares four low-cost GPS receivers, in order to determine the most suitable receiver for position assessment under different forest canopy covers, in terms of ease of use, accuracy, and reliability. A total of 33 positional assessments were gathered per receiver, plot, and method, in 18 forest locations. Data were described and analyzed through a sample c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 14 publications
1
34
0
2
Order By: Relevance
“…Na área florestal, a tecnologia GPS tem tido diversas aplicações, tais como: instrumento de atualização de bases cartográficas de empresas florestais e locação de experimentos ambientais (RODRIGUES-PEREZ et al, 2006), na localização e marcação de árvores em inventário florestal (FIGUEIREDO et al, 2008), no mapeamento simultâneo das árvores e das colheitadeiras (harvesters) florestais (OHMA et al, 2007), no mapeamento e danos causados por incêndios florestais (EL-SHEIMY & WRIGHT, 2003) e no microplanejamento florestal (BERNARDI & PONTES, 2006). Naesset (2001) comentou que a precisão dos resultados nas determinações de posicionamento depende do procedimento utilizado e do aparelho receptor GPS usado e como resultado pode-se obter precisão de 10 metros (posicionamento absoluto) até milímetros (posicionamento usando sinais L1 e L2).…”
Section: Introductionunclassified
“…Na área florestal, a tecnologia GPS tem tido diversas aplicações, tais como: instrumento de atualização de bases cartográficas de empresas florestais e locação de experimentos ambientais (RODRIGUES-PEREZ et al, 2006), na localização e marcação de árvores em inventário florestal (FIGUEIREDO et al, 2008), no mapeamento simultâneo das árvores e das colheitadeiras (harvesters) florestais (OHMA et al, 2007), no mapeamento e danos causados por incêndios florestais (EL-SHEIMY & WRIGHT, 2003) e no microplanejamento florestal (BERNARDI & PONTES, 2006). Naesset (2001) comentou que a precisão dos resultados nas determinações de posicionamento depende do procedimento utilizado e do aparelho receptor GPS usado e como resultado pode-se obter precisão de 10 metros (posicionamento absoluto) até milímetros (posicionamento usando sinais L1 e L2).…”
Section: Introductionunclassified
“…However, they added that this method can also be inaccurate in the forest. Rodriguez-Perez et al (2007) pointed out that the use of GPS in the forest ecosystem introduces problems related to signal reception under the forest canopy, including the visibility of satellites in a given territory at the time of measurement. Coulter et al (2006) were convinced that the best method to set the maintenance plan of a forest road network is a combination of heuristic analysis, analysis of financial costs and impacts on the environment, and "expert judgment".…”
Section: Introductionmentioning
confidence: 99%
“…The main factors that cause increased sediment delivery to forest streams are removing plant cover along the forest road pathway, compaction of the soil in the roadbed, interception of surface and sub-surface flows, constructions of cutslopes, and alteration of hillslope water pathways (Tague & Band 2001). Sediment delivered to forest streams cause water resource pollution, filling dams and may have impacts on aquatic habitat (Damian 2003, Refahi 2006, Khalilpoor et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The main factors that cause increased sediment delivery to forest streams are removing plant cover along the forest road pathway, compaction of the soil in the roadbed, interception of surface and sub-surface flows, constructions of cutslopes, and alteration of hillslope water pathways (Tague & Band 2001). Sediment delivered to forest streams cause water resource pollution, filling dams and may have impacts on aquatic habitat (Damian 2003, Refahi 2006, Khalilpoor et al 2008.Three methods are typically used to measure sediment produced from forest roads: (1) measurement in natural conditions with natural precipitation events (e.g., direct measurements from outlet of live streams culverts or using sediment traps - (2007) showed that cutslope areas are responsible for about 9% of the total road segment sediment production. Luce & Black (1999) examined the relationship between sediment production and road attributes such as distance between culverts, road gradient, road texture, and vegetation cover on cutslope.…”
mentioning
confidence: 99%